Industri Pengolahan Terasi dan Upaya Pemasarannya di Desa Sendangsikucing, Rowosari, Kendal - Tasa Nur Fadilah; Nala Rahmania; Zulfa Dwi A; Fadilla Qurrata A; Maryatul Kibtiyah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The purpose of this study was to determine the process of making shrimp paste in Sendangsikucing Village. The research method used was interview and observation techniques. With the aim of providing a systematic description of the facts and characteristics of the object being studied accurately. The processing of shrimp paste is carried out at home or individually. The processing of making shrimp paste itself begins with drying rebon shrimp, pounding, extracting, fermentation and finishing or printing.